Iran and China a new approach to their bilateral relations - Azad, Shirzad (Lexington Books, 2017)
Because of their historical roles and politico-economic significance in contemporary international politics, Iran and China have perpetually been in the crosshairs of both policy circles and interested observers in almost every other part of the world. Crucial interactions touching upon any aspect of Tehran–Beijing ties, from diplomatic and military links to economic and cultural connections, have especially been in the limelight of such riveting inquisitiveness which has often given rise to a flurry of rash comments, sensational claims, and impetuous conclusions. But a detached probe into critical developments involving Iran and China, however, elucidates this rather inconvenient eventuality that the relations between the two important countries are not essentially based on pivotal principles and clear-cut commitments, nor do their ties really rest on tenuous thoughts and flimsy foundations devoid of any common interests in short term or well-conceived objectives in long run. In the same way, the two political systems in Tehran and Beijing may ultimately end up each contributing to a separate pole of power regionally and internationally rather than moving faithfully and steadfastly in lockstep with what it requires them to truly materialize their more recent aspiration and design to move toward achieving a very close strategic partnership.--Provided by publisher.